Assessing Genetic Variability for Root Traits and Identification of Trait‐Specific Germplasm in Chickpea Reference Set. Issue 5 (1st September 2015) - Lalitha, N.; Upadhyaya, Hari D.; Krishnamurthy, L.; Kashiwagi, J.; Kavikishor, P.B.; Singh, S.
ABSTRACT: Chickpea ( Cicer arietinum L.) is a major grain legume cultivated largely on residual soil moisture in the arid and semiarid regions of the world. Terminal drought stress is one of the major causes of yield loss, and a deep root system has been recognized as one of the most important traits for enhancing drought adaptability. To diversify the current genetic base of root traits, the present study explored the variation for root traits in the reference set of chickpea ( n = 300) germplasm. Genetic variability for root traits at 35 d after sowing was assessed using a polyvinyl chloride (PVC) cylinder culture system in two postrainy seasons. Largest genetic variability was observed for dry weights of shoot (broad‐sense heritability [ h 2 ] = 0.69–0.74) and root ( h 2 = 0.52–0.70). For root‐length density ( h 2 = 0.42–0.43) and root/total‐plant dry‐weight ratio ( h 2 = 0.32–0.54), h 2 values were moderate but the variation was large, indicating scope for selection. The performance of the reference set accessions was identified for each of key traits. Accessions with the best root‐length densities along with root and shoot dry weights were found to originate from the Mediterranean region and western Asia emphasizing the importance of whole collection from these regions for superior root traits. This study identified 23 new accessions for widening the parental base in further drought tolerance breeding efforts and identified superior traits in already adapted genetic backgrounds.